Australia's cognitive, affective and conative destination image: an Emirati tourist perspective. Issue 1 (5th March 2018) - Michael, Noela; James, Reynold; Michael, Ian
Abstract : Purpose: The purpose of this study is to understand the destination image perceptions about Australia – a Western culture country – as held by the rapidly increasing, high spending, culturally dissimilar new segment of travellers, the Emiratis[1 ] from the United Arab Emirates (UAE). Design/methodology/approach: A qualitative methodology was used to understand the cognitive, affective and conative images of Australia. A structured categorisation matrix was used to analyse the data so that only aspects fitting the matrix were selected. Findings: Within the cognitive variable, Australia was found to be pleasant, family oriented, a fun place, laid back and the local people friendly. From an affective factor perspective, Australia was seen as being exciting, because of the variety of activities available for these tourists. Exciting was expressed by words like fantastic, amazing and extreme experience. In terms of the conative variable most of the Emirati tourists expressed strong feelings to go back to Australia and to even re-visit with friends. They also mentioned that they would recommend Australia to family and friends. Research limitations/implications: A limitation of this study was that our sample comprised informants mainly from the Emirates of Abu Dhabi and Dubai, the two largest Emirates of the nation. The study offers destination marketing organisations' (DMOs) insights into Emirati travellers' perceptions about Australia, which would benefit destination marketing. Originality/value: This study examines the under researched area of how Australia – with its liberal Western culture – could be better marketed to the growing numbers of culturally conservative, high spending Emirati outbound tourists from the officially Islamic UAE, and also more generally to the socio-culturally homogeneous Gulf Cooperation Council region that the UAE is part of. Whilst destination image is an intensively analysed topic within the realm of tourism research, and reportedly a powerful influence on destination choice, the extant literature on how Australia is perceived as a travel destination by Emiratis is scant. For DMO's attempting to attract wealthy Emirati tourists into Australia, this research is valuable and timely, as several Emiratis are seeking newer travel destinations away from the Western hemisphere, where the general anti-Arab/Islamic sentiments are currently quite strong.